2020
DOI: 10.1080/21528586.2021.1909495
|View full text |Cite
|
Sign up to set email alerts
|

Hey, it is Rough Out Here”: A Resilience Lens on the Biopsychosocial Circumstances of Homeless Older Persons in the City of Tshwane

Abstract: The biopsychosocial circumstances of homeless older persons (male and female persons, 55 years and older), specifically considered from a resilience lens, are inadequately described within the South African context. This study explored and described the biopsychosocial circumstances of homeless older persons in the City of Tshwane from a resilience lens. A qualitative research approach, operationalised through a collective case study, was implemented with 34 older persons across different research sites in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Likewise, an earlier study by HelpAge International ( 2011 ) revealed that homeless older people in Ethiopia used begging as their primary source of income to survive. Consistent with our findings in Ethiopia, older homeless adults in South Africa used a variety of coping mechanisms that included both intrapersonal and interpersonal strategies (Geyer, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Likewise, an earlier study by HelpAge International ( 2011 ) revealed that homeless older people in Ethiopia used begging as their primary source of income to survive. Consistent with our findings in Ethiopia, older homeless adults in South Africa used a variety of coping mechanisms that included both intrapersonal and interpersonal strategies (Geyer, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…Yet, in the absence of public income support for older adults and in light of persistent age discrimination, a significant portion of older adults who migrate to urban areas end up homeless (HelpAge International, 2013 ). Although a few studies have examined the plight of homeless older adults in other Sub‐Saharan nations such as Nigeria (Geyer, 2021 ) and South Africa (Hellandendu, 2014 ), the struggles of homeless older adults in Ethiopia have received little attention. Likewise, while there has been some attention to the push factors contributing to the growing problem of homelessness in the continent (Makiwane et al, 2010 ; Speak, 2020 ), less attention has been given to older adults' responses to homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…In the developing world, including South Africa, most of the recent studies on the homeless considered specifically from a social work perspective have been limited to the Gauteng province. For example, in 2021 Mahlangu and Kgadima (2021) published a study that focused on the social exclusion and associated stigma of homeless adults in the CoT; Geyer (2020) published work on the resilience of HOPs in the CoT; however, these studies reflect the context of pre-COVID-19. Moyo, Patel and Ross (2015) published on homelessness and mental illness in Hillbrow in the City of Johannesburg.…”
Section: Literature Overviewmentioning
confidence: 99%
“…A description of the characteristics and the face of the homeless population in the City of Tshwane (CoT) 1 is not described in this article, as it has been described elsewhere (cf. Makiwane, Tamasane, and Schneider 2010;Mashau and Kritzinger 2014;Renkin 2015;Kriel, Tembe, and Mashava 2017;Marcus et al 2020;De Beer and Hugo 2021;Geyer 2021;Scheibe et al 2021). In the article, the terms homeless persons and homeless people refer to people who find themselves on the streets and are unable to secure shelter for themselves.…”
Section: Introductionmentioning
confidence: 99%